2020
DOI: 10.1002/ijgo.13380
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of offspring and mothers with gestational diabetes treated with metformin or glibenclamide: A randomized controlled trial

Abstract: Synopsis A 9‐year follow‐up of a randomized controlled trial showed metformin to have better neonatal outcomes than glibenclamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This study also did not find any difference in terms of the likelihood of having a weight for height percentile greater than the 85 th percentile in the children of metformin-exposed mothers as compared to insulin treated counterparts. A recent study from India reported nine years of follow-up data of the offspring of mothers who were randomized either to metformin or glibenclamide during their GDM management[ 16 ]. They found no difference in BMI, WC or visceral fat distribution between the treatment groups.…”
Section: Long-term Effects Of Metformin On Offspring Of Mothers With Gestational Diabetesmentioning
confidence: 99%
“…This study also did not find any difference in terms of the likelihood of having a weight for height percentile greater than the 85 th percentile in the children of metformin-exposed mothers as compared to insulin treated counterparts. A recent study from India reported nine years of follow-up data of the offspring of mothers who were randomized either to metformin or glibenclamide during their GDM management[ 16 ]. They found no difference in BMI, WC or visceral fat distribution between the treatment groups.…”
Section: Long-term Effects Of Metformin On Offspring Of Mothers With Gestational Diabetesmentioning
confidence: 99%